2016
DOI: 10.1115/1.4033550
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of I&C Design With the Obligatory Consideration of Human Factors: A Project Management Approach

Abstract: Human factors engineering (HFE), such as other engineering disciplines involved in plant design, cannot be considered retroactively. The engineering principles and methods derived from deep knowledge of the cognitive and perceptual capabilities and limitations of the plant’s “human element” are applied instead throughout the plant design. Focusing HFE efforts, the plant’s HMI is designed to ensure effective and error-free performance of the monitoring, control, and administrative tasks allocated to the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…There is also significant research regarding "teamwork", with over 100 articles found. However when exploring the union of uncertainty, design, and teamwork, there is very little existing research that explores these three unique aspects, with only 6 articles [6][7][8][9][10][11] found including these three keywords.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…There is also significant research regarding "teamwork", with over 100 articles found. However when exploring the union of uncertainty, design, and teamwork, there is very little existing research that explores these three unique aspects, with only 6 articles [6][7][8][9][10][11] found including these three keywords.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%